Las cautivas de la casa real de Troya: Casandra y Polixena - Álvarez Espinoza, Nazira (2015)
This paper analyzes gender relations in Euripide’s tragedies The Trojan Women and Hecuba regarding rape, ritual sacrifice and physical, sexual and symbolic violence against the royal captives Polixena and Kassandra as they both face their destiny as slaves after the Troyan war.